Design of a Monolithic Inductor and Its Influence on the Oscillator Design. Issue 3 (4th May 2022) - Thakur, Atul; Chatterjee, Shouri
Abstract : Reliability of a wireless communication system depends on the performance metric of the oscillators employed. In this paper, we have discussed the commonly used oscillator architectures, their equivalent RLC circuits and the influence of the inductor performance on the oscillator design. Inductors designed for the oscillators are fabricated in 180 nm CMOS process. Inductors are implemented with 20 k Å top metal layer of the P1M6 layer architecture. Two-turns twisted and 3-turns spiral shape inductors are fabricated with and without the substrate shield, respectively. Twisted shape inductor with the floating substrate shield has higher Q-factor due to low substrate loss. To further validate the performance of inductors, digitally controlled oscillators (DCO's) are designed around the inductors and simulated for its phase noise performances. Inductors are designed on a (lossy) substrate with a resistivity of 2 Ω-cm. The twisted shape inductor has a Q-factor of 5.23 at the operating frequency of 1.8 GHz for the inductance value of 2.8 nH and has a self-resonance frequency (SRF) of 10 GHz. Whereas spiral shape inductor achieves the maximum Q-factor of 1.18 for the inductance value of 3.4 nH with SRF of 12.5 GHz. DCO's implemented with the designed twisted and spiral shape inductors has the phase noise of − 107 and − 92 dBc/Hz, respectively, at an offset of 1 MHz from 1.8 GHz of the center frequency.